Chemistry - Chang, Raymond; Goldsby, Kenneth A. (McGraw Hill, 2016)
Features a straightforward, clear writing style and proven problem-solving strategies. This book offers a firm foundation in chemical concepts and principles while presenting a broad range of topics in a clear, concise manner